Skin neoplasia early detection by fractal analysis of images and 3D inspection - Costa, Manuel F. M. (2021)
Early detection of skin cancer is fundamental to a successful treatment. Changes in the shape, including the relief, of skin lesions are an indicator of a possible malignity. As well and image processing optical microtopographic inspection of skin lesions can be used to identify diagnostic patterns of benign and malign skin lesions. Statistical parameters like the mean roughness (Ra) may allow the discrimination between different types of lesions and degree of malignity. Fractal analysis of bi-dimensional and 3D images of skin lesions can validate or complement that assessment by calculation of its fractal dimensions (FD). On the study herein reported the microtopographic inspection of the skin lesions were performed using the optical triangulation based microtopographer developed at the Physics Department of the University of Minho, MICROTOP.03.MFC. Images of the skin lesions were digitized and processed in order to calculate fractal parameters. The patients that participated in this research work were men and women older than 15 years with the clinical and histopathology diagnoses of: melanoma, basocellular carcinoma, epidermoide carcinoma, actinic keratosis, keratoacantosis and benign nevus. The combination of the rugometric evaluation and fractal geometry characterization, both 2D and 3D, provides valuable information about the malignity of skin lesions and type of lesion.